Motivasi Karir, Lama Pendidikan, dan Biaya Pendidikan terhadap Minat Mahasiswa Akuntansi Mengikuti Pendidikan Profesi Akuntansi - Inayah Inayah; Dyah Ratnawati (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of career motivation, length of education and education costs on the interest of accounting students to participate in the Accounting Profession Education (PPAk). This research method is a quantitative method. Data analysis used multiple regression analysis which the calculation process used the SPSS 25 program. The hypothesis test used was the coefficient of determination (R2 test), simultaneously (F test), and partial test (t test). The population in this study were accounting students at the 2018 Veterans National Development University in East Java, with a total of 224 students. The results showed, based on the results of the T test, namely, a) the career motivation variable on student interest had a tcount of 3.248 > from ttable of 1.977 and a significance value of 0.001 <0.05; b) the variable length of education on student interest has a tcount of 4.364> from a t-table of 1.977 and a significance value of 0.000 <0.05; c) the variable cost of education on student interest has a tcount value of 0.576 < from a ttable of 1.977. In conclusion, career motivation and length of education have a significant effect on the interest of accounting students to take PPAk, while the cost of education has no significant effect on student interest in PPAk. Keywords: Cost of Education, Length of Education, Interest of Accounting Students Following PPAK, Career Motivation